1911 Basket Ball Team C.P.S - Frank Aston::::::photographer::: (1911)
Group portrait,1911 men's basketball team in uniform with 'C Polytechnic' banner; on outdoor basketball court. Published in Polytechnic J. (v.6, no.8, June 1911) 'Boys' Basketball.'